2007
DOI: 10.1103/physrevb.76.035403
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo calculations of the surface energy of an electron gas

Abstract: We present quantum Monte Carlo calculations of the surface energy of the electron gas ͑jellium͒. Our results agree with the best estimates obtained by other methods, thus appearing to resolve the controversy which currently exists and paving the way for future simulations of real surface systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…Figure 1 shows surface energy enhancements relative to LSDA. The likely "range of the possible" for e surf xc extends from TPSS meta-GGA [3,7] or RPA+ [23] at the low end of what is possible (in agreement with the most recent Quantum Monte Carlo calculations [24]) to the RPA-like Pitarke-Perdew (PP) [25] value at the high end. The TPSS value probably provides the best value that a GGA should try to achieve.…”
supporting
confidence: 80%
“…Figure 1 shows surface energy enhancements relative to LSDA. The likely "range of the possible" for e surf xc extends from TPSS meta-GGA [3,7] or RPA+ [23] at the low end of what is possible (in agreement with the most recent Quantum Monte Carlo calculations [24]) to the RPA-like Pitarke-Perdew (PP) [25] value at the high end. The TPSS value probably provides the best value that a GGA should try to achieve.…”
supporting
confidence: 80%
“…Surface correlation energies 18 and surface exchange-correlation energies 19,20 have been obtained using extrapolated values to infinite size. In general, the values obtained for correlation surface energies obtained with spheres are consistent with the latest DMC results for jellium slabs 21 and other methods, but differ to some extent from the original DMC results from slab geometries 22 .…”
Section: Pacs Numberssupporting
confidence: 76%
“…This unexpected success of the LD approximation (for exchange and correlation) suggested that we try to understand what was behind it. Quantum Monte Carlo calculations confirmed the LD results many years later (Wood et al, 2007). 21 It has been shown (Colonna and Savin, 1999) that results for the He and Be series atoms using the two schemes are similar.…”
mentioning
confidence: 74%